YOGA AND CROSS-CULTURAL COMMUNICATION IN MULTICULTURAL ENVIRONMENTS - Ni Luh Sinar Ayu Ratnadewi; I Nyoman Sueca (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
The journal focused on investigating the transformative role of yoga within diverse cultural contexts. In an era characterized by unprecedented multiculturalism and global interaction, yoga emerges as a powerful cultural bridge, enhancing cross-cultural understanding and fostering inclusion. This journal invites rigorous academic exploration of yoga's multifaceted influence. It welcomes research spanning historical roots, cultural adaptations, and psychological dynamics of yoga practice within multicultural societies. Interdisciplinary dialogue is encouraged, with a focus on psychology, communication, anthropology, sociology, and cultural studies, providing a comprehensive view of yoga's cross-cultural impact. Ethical considerations related to the practice and propagation of yoga are explored, alongside practical applications in promoting unity, well-being, and psychological resilience within diverse communities. The journal also engages with future directions in yoga research and application. Committed to academic rigor,